Modelling techniques for delamination and fracture of composites - Curiel-Sosa, J.L.; Tafazzolimoghaddam, Behrooz; Navarro-Zafra, Joaquin; Akbar, Mahesa; Abdullah, Nur Azam; Ahmad, Meor iqram Meor (INEGI-Instituto de Ciência e Inovação em Engenharia Mecânica e Gestão Industrial Rua Dr Roberto Frias, 2017)
In this study, modelling techniques based on new extended finite element methodologies for the study of fracture, in general, and delamination in composites, in particular are presented. Recent approaches have successfully modelled fracture without the need of continuing refinement of the finite element mesh. This is an outstanding advantage in terms of reliability and computational cost. Details of the initiation criteria and evolution of a crack are provided. It is argued that the strategies presented herein would appeal to the engineering practice as reliable techniques for structural integrity assessment of novel designs. The results are validated against data from the literature showing the robustness and accurateness of the techniques presented.